Global business associations - Ronit, Karsten (London : Routledge, 2018)
"Global business tends to be perceived as a number of individual but powerful multinational corporations, capable of controlling markets and influencing political decisions; in fact, global business is highly organized through a plethora of associations that bring together competing companies and conflicting national businesses. Indeed, global business associations have a long history and, with accelerated globalization, further opportunities emerge for unified business action. This book fills a significant gap in the current literature, examining the pivotal role of global business associations and providing a concise and accessible overview of their different functions in a range of institutional contexts. Beginning by clarifying the concept of global business associations, the author puts their role into a historical and contemporary context in which their economic, social and political functions are sketched. Their historical origin is outlined, including the proliferation of global associations in the twentieth and twenty-first centuries. He then moves on to explore and analyse the different types of actors, explaining key categories and their place in the organization of global business with chapters on peak associations (e.g. ICC and WEF), industry associations, alliance associations, as well as clubs and think tanks, and facilitators. Covering the history, current role and future evolution of this dynamic category of associations, this work will be essential reading for students and scholars of IPE, international relations, international organizations and global governance"--
Peak associations -- Industry associations -- Alliances of corporations and associations -- Clubs and think tanks -- Facilitators -- Conclusion.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 24, 2018).
Karsten Ronit is associate professor at the Department of Political Science, University of Copenhagen. He has studied the role of organized business and other interest groups in a range of domestic, regional and global contexts. He has published many articles and books on these subjects, most recently Global Consumer Organizations with Routledge.
eBooks on EBSCOhost
Keywords: International business enterprises -- Societies, etc; Entreprises multinationales -- Associations; BUSINESS & ECONOMICS -- Industries -- General; POLITICAL SCIENCE -- General; POLITICAL SCIENCE -- History & Theory; POLITICAL SCIENCE -- International Relations -- General